Analysis of the Group of Pediatric Patients With Relapsing-Remitting Multiple Sclerosis: Data From the Czech National Registry - Vališ, Martin; Pavelek, Zbyšek; Novotný, Michal; Klímová, Blanka; Šarláková, Jana; Halúsková, Simona; Peterka, Marek; Štětkárová, Ivana; Štourač, Pavel; Mareš, Jan; Hradílek, Pavel; Ampapa, Radek; et al. (Frontiers in Neurology, 2022)
Importance: Multiple sclerosis can also affect children. Approximately 3-10% of patients develop multiple sclerosis before the age of 16. Objective: The aim of this analysis is to describe the characteristics of pediatric patients with multiple sclerosis who started their treatment with disease-modifying drugs in 2013-2020, with data obtained from the Czech National Registry of patients with multiple sclerosis. Design and setting: A method of retrospective analysis conducted with 134 pediatric patients with multiple sclerosis was used. Results: The findings reveal that the mean age at the date of the introduction of the first disease-modifying drugs treatment is 15.89 years, and gender does not play any role. In addition, moderate (51.6%) and mild (45.2%) relapses are predominant in these young patients. 75% of patients will not experience a confirmed progression of the expanded disability status scale within 54.7 months from starting the treatment. Furthermore, the results confirm that the first-choice treatment is interferon beta-a and glatiramer acetate, which is common for adult patients. However, some factors, such as a low efficacy or a lack of tolerance, among children may discontinue the treatment. Conclusion: More attention should be paid to researching novel disease-modifying drugs for this target group.